Potential growth: A global database - Sinem Kılıç Çelik; M. Ayhan Kose; Franziska Ohnsorge; F. Ulrich Ruch (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
Potential growth - the rate of expansion an economy can sustain at full capacity and employment - is a critical driver of development progress. It is also a major input in the formulation of fiscal and monetary policies over the business cycle. This paper introduces the most comprehensive database to date, covering the nine most commonly used measures of potential growth for up to 173 countries over 1981-2021. Based on this database, the paper presents three findings. First, all measures of global potential growth show a steady and widespread decline over the past decade, with all the fundamental drivers of growth losing momentum over time. In 2011-21, potential growth was below its 2000-10 average in nearly all advanced economies and roughly 60 percent of emerging market and developing economies. Second, adverse events, such as the global financial crisis and the COVID-19 pandemic, contributed to the decline. At the country-level also, national recessions lowered potential growth even five years after their onset. Third, the persistent impact of recessions on potential growth operated through weaker growth of investment, employment, and productivity
Keywords: E30; E32; E37; O20; 330; production function; filters; growth expectations; developing economies